Deriving angular frequency for simple harmonic motion

  • Thread starter AlexYH
  • Start date
  • #1
1
0

Homework Statement


Derive the equation for angular frequency for simple harmonic motion of a spring.


Homework Equations


Derive omega = sqrt(k/m) from F = -kx
(sorry i don't know how to use notation)


The Attempt at a Solution


I asked my teacher how to do this, and he used some crazy math I didn't learn yet, including Euler's identity and differential equations. I'm in an AP calculus bc class, and i understand differential equations, just not some aspects. Does anyone know a simple solution for this? Thanks in advance
 

Answers and Replies

  • #2
12
0
If [tex]F=ma[/tex] and [tex]F=-kx[/tex]

Then [tex]ma=-kx[/tex] (by equating the forces.)

Which can be also written as [tex]ma+kx=0[/tex]

or [tex]a+\frac{k}{m}x=0[/tex]

Now if x is displacement, differentiating once with respect to time will give you velocity of the spring and then differentiating again with respect to time will give acceleration.

Displacement of a spring can be given by

[tex]x=A * Cos (\omega t)[/tex]

where A is the Amplitude of motion and [tex]\omega [/tex] is the angular frequency

Now Differenting once will give velocity;

[tex]v=-A\omega Sin(\omega t)[/tex]

and again to give acceleration

[tex]a=-A \omega^{2} Cos(\omega t)[/tex]

Now substituting our formula for Acceleration and displacement into our equation of motion

[tex]a+\frac{k}{m}x=0[/tex]

Gives [tex]-A \omega^{2} Cos(\omega t) +\frac{k}{m}A Cos (\omega t)=0[/tex]

Which can be rearranged to;

[tex]A(-\omega^{2} +\frac{k}{m})Cos(\omega t)=0[/tex]

Can get rid of the [tex]A[/tex] and [tex]Cos(\omega t)[/tex]

which leaves [tex]-\omega^{2} +\frac{k}{m}=0[/tex]

which can be rearranged to [tex]\omega=\sqrt{\frac{k}{m}}[/tex]
 
  • #3
rock.freak667
Homework Helper
6,223
31
If [tex]F=ma[/tex] and [tex]F=-kx[/tex]

Then [tex]ma=-kx[/tex] (by equating the forces.)

Which can be also written as [tex]ma+kx=0[/tex]

or [tex]a+\frac{k}{m}x=0[/tex]

or from here

that is in the form [itex]a=-\omega^2x[/itex]

where [itex]\omega^2=\frac{k}{m}[/itex]
 

Related Threads on Deriving angular frequency for simple harmonic motion

Replies
1
Views
2K
Replies
3
Views
994
  • Last Post
Replies
1
Views
674
  • Last Post
Replies
3
Views
8K
  • Last Post
Replies
3
Views
1K
  • Last Post
Replies
3
Views
4K
Replies
25
Views
5K
Replies
5
Views
1K
Replies
1
Views
4K
Replies
1
Views
2K
Top